Pokémon 3 : the movie - Tajiri, Satoshi, 1965- (Viz Media, LLC, 2016)
Little Molly Hale has always led a lonely life, but things only get worse for her when the long-lost Uknown cause her father to mysteriously vanish one day. But things start to seem brighter when the power of the Uknown starts to change the world around her into a fantasy land. She soon lives in a crystal palace, and has the Legendary Entei as a dad. There's only one thing missing rom the equation, a mother.